Baicalin inhibits IL-1β-induced ferroptosis in human osteoarthritis chondrocytes by activating Nrf-2 signaling pathway - Jiuxiang Liu; Hao Zhou; Jiangqi Chen; Qiang Zuo; Feng Liu (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Background Osteoarthritis (OA) is a common degenerative disease involving articular cartilage, in which ferroptosis of chondrocytes plays an important role. Baicalin (BAI) exerts regulatory effects in a wide range of orthopedic diseases including OA, but its effect on ferroptosis of chondrocytes (CHs) is still unclear. The purpose of this study was to determine the effect of BAI on ferroptosis in human OA chondrocytes (OACs), and to explore its possible mechanism. Methods CHs were treated with IL-1β (10 ng/mL) to simulate inflammation in vitro. Immunofluorescence, quantitative RT-PCR, Western blotting and cell viability assay were performed to evaluate the impacts of BAI on Fe2+ level, mitochondrial dysfunction, ferroptosis-related proteins, oxidative stress and cytotoxicity in CHs. Additionally, siRNA was made use of to knock out nuclear factor E2-related factor 2 (Nrf2) to analyze the role played by Nrf2 in BAI-induced CH ferroptosis. Results BAI eliminated IL-1β-induced Fe2+ accumulation, changes in mitochondrial membrane potential and ferroptosis-related protein GPX4, SLC7A11, P53 and ACSL4 levels, as well as reactive oxygen species (ROS), lipid peroxidation (LPO) and malondialdehyde (MDA) accumulation in CHs. Besides, BAI reversed IL-1β-induced decrease of Collagen II and increase of MMP13 in CHs. Meanwhile, BAI attenuated IL-1β-induced CH toxicity and promoted Nrf2 antioxidant system activation. When Nrf2 was knocked down by siRNA, the effects of BAI on IL-1β-induced ferroptosis-related proteins and antioxidant stress in CHs were significantly weakened. Conclusions This study demonstrates that IL-1β can induce CH ferroptosis. BAI is able to inhibit IL-1β-induced CH ferroptosis and ECM degradation, and the specific mechanism may be that it can inhibit IL-1β-induced CH ferroptosis by activating Nrf2 antioxidant system to attenuate the accumulation of intracellular ROS and lipid ROS.